Konseling Multikultural Sebagai Pendekatan Studi Terorisme - Sri Suwartini; Erham Budi Wiranto (Jurnal Dakwah: Media Komunikasi dan Dakwah, 2021)
The purpose of this research is to describe the scientific stance of multicultural counseling and its contribution to Terrorism Studies. Attempts are made by performing a literature study on three topics: multiculturalism, multicultural counseling, and terrorism studies. This study found that Multicultural Counseling can be an appropriate approach in Terrorism Studies because Terrorism Studies currently lack the perspective of terror perpetrators' subjectivity. This need can be filled by Multicultural Counseling with its scientific qualities and distinctive capabilities.Studi ini bertujuan menjelaskan kedudukan keilmuan Konseling Multikultural serta kontribusinya dalam Studi Terorisme. Upaya menjelaskan hal tersebut ditempuh dengan cara melakukan review literatur seputar tiga isu, yaitu multikulturalisme, konseling multikultural, dan studi terorisme. Studi ini menemukan bahwa Konseling Multikultural dapat menjadi pendekatan yang baik dalam Studi Terorisme, sebab studi terorisme saat ini masih kekurangan perspektif subyektifitas pelaku teror. Konseling Multikultural dengan karakteristik keilmuan dan kemampuan khususnya mampu mengisi celah tersebut.